Factors affecting Japan in resolving the issue of jugun ianfu with South Korea through a ‘finally and irreversibly’ agreement between Japan and South Korea in 2016 - Constantya Astrid Permata Sari; Usmar Salam; Makarim Wibisono; Tahan Samuel Lumban Toruan (Universitas Pertahanan Republik Indonesia (UNHAN RI), 2022)
Jugun ianfu or comfort women is a term for women who are used to meet the sexual needs of Japanese soldiers during the colonial period until the end of World War II. After rejecting the program from the Asian Women’s Fund (AWF) which was formed by the Japanese government to resolve the issue of jugun ianfu, activists and the South Korean government urged Japan to resolve the issue again. However, the Japanese government did not give a positive response. In fact, in 2014 the investigative team under Shinzo Abe stated that the statement acknowledging the direct or indirect involvement of the Japanese military in the creation and management of the comfort station was not based on facts and was the result of negotiations with South Korea. However, in November 2015, the Foreign Ministers of Japan and South Korea met and agreed to resolve this issue by drawing up a 'Finally and Irreversibly' Agreement. The author uses a qualitative method with the main data source in the form of literature to analyze why the Japanese government finally softened and agreed to resolve the issue of South Korea's jugun ianfu by compiling a ‘Finally and Irreversibly’ Agreement. The changes that occurred on the part of the Japanese government were caused by various internal and external factors, such as economic problems faced by Japan, decisive action from South Korea, pressure from the United States, the strengthening of the economy and defense from China and the increasing nuclear capabilities of North Korea.